An overview of recent WHO classification and AJCC pTNM staging changes for testicular neoplasms and their impact on the handling and reporting of orchidectomy specimens. Issue 6 (June 2018) - Evans, Andrew J.
Abstract: The World Health Organization 2016 Classification of Testicular Tumours and the 8 th Edition of the American Joint Cancer Commission Staging Manual released in 2017 introduced a number of significant changes which impact the way pathologists will be expected to examine and report tumour-containing orchidectomy specimens. The purpose of this review is to highlight the changes to classification nomenclature and pathologic staging criteria for commonly encountered testicular neoplasms of either germ cell or sex-cord stromal origin and to provide an overview of resources available to assist pathologists in the task of providing complete and clinically relevant histopathology reports for orchidectomy specimens.